Optimalisasi Usaha melalui Pendampingan Penyusunan Laporan Keuangan bagi Pengusaha Minuman Sari Nanas - Virginia Nur Rahmanti; Husnul Hatimah; Nawira Amalia Assagaf; Rizka Beauty Tamara (Jurnal Pemberdayaan Umat, 2023)
Purpose: Community service activities in the form of assistance in preparing financial reports are held to help optimize business reporting for pineapple juice drink entrepreneurs in Blitar Regency. The main problem faced by entrepreneurs is the absence of a structured record of financial activities. This is triggered by the limited ability of entrepreneurs in identifying the components of product costs. Method: The mentoring program was carried out using the FGD mechanism which was divided into 5 groups with 5 members in each group. The FGD stages include problem identification, assistance in identifying product cost components, preparing financial reports, and evaluating. Results: The mentoring program which lasted for 6 months went well. Entrepreneurs realize that there are several cost components that have not been calculated as part of determining the selling price, such as depreciation expense for equipment and labor. As an implication, the estimated profit that has been calculated so far is still not fully accurate. After carrying out assistance in the preparation of simple financial reports, the entrepreneurs were finally able to present more accurate profit/loss reports so that during their evaluation they began to make adjustments to product sales management. Limitations: The community service program was carried out in the Kalikebo village area of Blitar regency to pineapple juice drink entrepreneurs. Mentoring activities are carried out on two main issues, namely cost identification, and preparation of simple financial statements Contributions: A series of mentoring activities carried out are expected to help pineapple juice drink entrepreneurs to determine more accurate selling prices, and help present simple financial reports as material for business evaluation